The Relationship Of Perceptions Of The Physical Work Environment, Workload And Wages With Contract Nurse Performance In Mataram City Hospital - I Made Amartha Bratasena; Sulaiman Lalu (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Nurses' performance as an integral part of the health care system is an important part that determines the quality of health services in hospitals. Nurses' performance in providing health services always gets special attention from patients. The perception of patients at the Mataram City Hospital shows that the performance of contract nurses is still considered low. There are several factors that can affect the performance of nurses in hospitals, including the physical work environment, workload and work wages. Objective: This study aims to determine whether there is a relationship between the physical work environment, workload and work wages with the performance of contract nurses at the Mataram City Hospital. Research Methods: The type of research used is quantitative research with a cross sectional approach. The research location is at the Mataram City Hospital. Data collection using a questionnaire. Respondents in this study were contract nurses at the Mataram City Hospital. The number of samples in this study were 80 respondents. Results: The results of the analysis showed that p < 0.05, this means that statistically the independent variables have an influence on the dependent variable, it can be concluded that there is a joint effect of perceptions of the work environment, workload and work wages with the performance of contract nurses at the Mataram City Hospital. Conclusion: this study concludes that there is a relationship between the physical work environment, workload and work wages with the performance of contract nurses at the Mataram City Hospital